Flora associated with transmission and sub-transmission power lines and their effects on biotic interactions: a case study in Honduras - Oyuela-Andino, Olvin (2023)
Transmission lines are structures built to provide energy for the population's consumption. However, these lines have a direct or indirect impact on ecosystems, altering their composition and biotic interactions. The objective of this study was to determine the floristic composition, pollination, and dispersal syndromes in the transmission and subtransmission lines Las Flores-Erandique (SFE), San Pedro Sula Sur-Naco (TSPS), and Danlí-Chichicaste (SChD) in Honduras. To conduct the vegetation characterization, the present flora within the 16 × 16 m right-of-way area was inventoried, and herbs, shrubs, and trees were collected. To establish the relationship between habitat and floral traits, and determine the pollination syndromes, flower size and corolla colors were based, while dispersal syndromes were determined considering different characteristics in fruit morphology, fruit type, color, and size, and based on botanical descriptions por considering different morphological characteristics of the fruits, type of fruit, color, and size, and based on the botanical descriptions. The predominant plant families in TSPS and SFE are Fabaceae, Rubiaceae, Malvaceae, and Melastomataceae, while in SChD they are Fabaceae, Asteraceae, and Malvaceae. Most plant species are used as food resources for birds, which can consume nectar, pollen, flowers, fruits, seeds, and also use fibers for nest construction. Bees are the most common pollinators, followed by small insects such as flies and ants. Zoochory is the predominant dispersal syndrome in all three study areas. Undoubtedly, plant-animal interactions should be considered in forest remnants where these structures have been located, as these mutualistic relationships contribute to the maintenance and well-being of biodiversity